Can monitoring training load deter performance drop-off during off-season training in Division III American football players? - Kildow, Ashley (My University, 2018)
PURPOSE: The aim of this investigation was to monitor the physical demands of Division III American football players during off-season training and to investigate differences in training responses between linemen and non-line and freshmen and upperclassmen players. METHODS: Twenty-three subjects (11 linemen, 12 non-line; 11 freshmen, 12 upperclassmen) from the university’s football team were recruited from an Exercise Science 100 conditioning class to participate in a 15-week off-season training program. Phase I consisted of concurrent strength and speed/endurance training (3-4 days/week) for 7 weeks. Phase II consisted of strength training and spring football practice (3-4 days/week) for 4 weeks. Strength and speed training continued for 3 weeks following spring practices. Countermovement jump, estimated 1 repetition maximum (1RM) bench press and back squat, 505 change of direction (COD), repeated 30-yard sprint anaerobic test (RSAT), and body weight were all measured prior, mid-way through, and following the study. RESULTS: A two-way ANOVA with repeated measures revealed no significant interaction between linemen and non-line players or between freshmen and upperclassmen for all performance variables (p > .05). Over the course of the study, RSAT % decrement, 505 COD times, and estimated 1RM performance for bench and squat significantly improved (p < .05). No significant changes were detected in CMJ, RSAT best time, or body weight (p > .05). CONCLUSION: Results indicate that linemen and non-line players and freshmen and upperclassmen did not respond significantly different to the present training program. Change of direction skill, speed, anaerobic capacity, and muscular strength all improved throughout the study. Further, all performance changes except vertical jump were maintained through the end of the study.
Keywords: Football; Exercise -- Physiological aspects -- Testing